Effect of mono‐(2‐ethylhexyl) phthalate (MEHP) on proliferation of and steroid hormone synthesis in rat ovarian granulosa cells in vitro. Issue 4 (24th November 2017) - Li, Na; Liu, Te; Guo, Kun; Zhu, Jian; Yu, Guangyan; Wang, Shuyue; Ye, Lin
Abstract : This study aimed to examine the proliferation of and secretion by rat ovarian granulosa cells (GCs) treated with mono‐(2‐ethylhexyl) phthalate (MEHP). Ovarian GCs were incubated with MEHP at concentration of 0, 25, 50, 100, and 200 µM for 24 hr. Cell viability was determined using the MTT Cell Proliferation Assay. Progesterone and estradiol production was evaluated by radioimmunoassay (RIA) and the expression of FSHR, PR, and ER was measured by immunocytochemistry. StAR, P450scc, 3β‐HSD, 17β‐HSD, and P450 arom mRNA levels were determined by RT‐PCR. MEHP markedly attenuated proliferation of GCs, increased expression of sex hormone receptors and key enzymes in progesterone production, and stimulated steroid hormone secretion. The result of these analyses demonstrates that MEHP exposure of GCs may have effects on rat ovarian functions. Abstract : The objectives of this work were to characterize mono‐(2‐ethylhexyl) phthalate (MEHP) cytotoxicity and effects on steroid hormone systems in rat ovarian granulosa cells (GCs) in vitro. Our results showed that MEHP inhibited the proliferation of GCs, increased sex hormone receptors and key enzymes in progesterone production, and caused abnormal steroid hormone synthesis, including increased progesterone and estradiol synthesis. Since MEHP is widely used in plastics, it has broad exposure potential in humans and should be studied further to establish the safety of this material.